Critical success factors for ERP implementation and upgrade - NAH, Fiona Fui-hoon (Institutional Knowledge at Singapore Management University, 2006)
Seven categories of critical success factors were identified from the ERP literature: (1) business plan and vision; (2) change management, (3) communication; (4) ERP team composition, skills and compensation; (5) management support and championship; (6) project management, (7) system analysis, selection and technical implementation. We conducted a case study of two organizations that had implemented and upgraded ERP systems. We adopted Markus and Tanis' four-phase model and compared the importance of these critical success factors across the phases of ERP implementation and upgrade. The importance of these factors across the phases of ERP implementation and upgrade is very similar. 'Business Plan and Vision' and 'Top Management Support and Championship' are critical during the Chartering phase. 'ERP Team Composition, Skills and Compensation,' 'Project Management' and 'System Analysis, Selection and Technical Implementation' are most important during the Project phase. 'Change Management' and 'Communication' are very important during the Project and Shakedown phases.